BARRIERS OF COMMUNITY-BASED TUBERCULOSIS ACTIVE CASE FINDING ACTIVITIES AT HEALTH VOLUNTEER LEVEL IN BANTUL DISTRICT, INDONESIA; AN IMPLEMENTATION RESEARCH (Berita Kedokteran Masyarakat (BKM), 2020)
Tuberculosis (TB) incidence still quite high over the world and Indonesia ranks third highest in the world. Bantul district the TB case finding in 2017 was 39.64%, under the national target in 70% rate. Along with the WHO End TB goal by 2035 encouraging more massive findings of TB cases, Active Case Finding (ACF) is increasingly recognized as a complement to Passive Case Finding (PCF). Involvement of Community Health Volunteers (CHVs) in the TB case finding has proven as one of an effective strategy to capture the presumptive TB cases. Meanwhile, CHVs performance has not been optimal, reflected from the low TB detection rate. Little is known about contextual factors that influence their implementation and perceptions regarding the involvement of CHVs in TB ACF. This study aims to explore the barriers of community-based TB ACF at health volunteer level. The study design was qualitative study. The research sample was taken by purposive sampling. Data collected by conduct IDI for health provider and FGD for CHVs. The results show there are several factors that influence implementation outcomes formulated in multilevel framework. The barriers in structural factors including lack of stake holder commitment following with lack of funding. From PHC factors the barriers are unclear organization of TB team, lack of communication with CHVs, over workload in PHC staff, and not every PHC have monitoring and evaluation for CHVs. While from CHV factors the barrier comes from different knowledge level and lack of confidence due to the gap of CHV training in every PHC, also they still facing stigma in community and lack of coordination with health provider. Then from the program factors there is different guidelines for community-based TB ACF that affected to unequally program delivery, this result in not optimal in conducted the TB ACF. Strong collaboration between CHVs and PHC is needed in the handling of TB cases but it still needs to pay attention to the local context and the resources. Although it is recognized the importance of CHV in TB case finding, barriers are still found in every factors and need appropriate intervention to enhance CHV performance in supporting community-based TB ACF.